2021
DOI: 10.1101/2021.01.15.426911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mRNA vaccine-elicited antibodies to SARS-CoV-2 and circulating variants

Abstract: To date severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has infected over 100 million individuals resulting in over two million deaths. Many vaccines are being deployed to prevent coronavirus disease 2019 (COVID-19) including two novel mRNA-based vaccines1,2. These vaccines elicit neutralizing antibodies and appear to be safe and effective, but the precise nature of the elicited antibodies is not known3–6. Here we report on the antibody and memory B cell responses in a cohort of 20 volunteers who … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
314
1
4

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(353 citation statements)
references
References 66 publications
34
314
1
4
Order By: Relevance
“…A recent study comparing humoral immunity generated by mRNA vaccinees (mRNA-1273 or BNT162b2) and individuals recovered from natural infection observed similarities in antibody binding titers and plasma neutralization capacity (36). Furthermore, this study also observed similar frequencies of RBD-specific memory B cells between vaccinees and infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing humoral immunity generated by mRNA vaccinees (mRNA-1273 or BNT162b2) and individuals recovered from natural infection observed similarities in antibody binding titers and plasma neutralization capacity (36). Furthermore, this study also observed similar frequencies of RBD-specific memory B cells between vaccinees and infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that mutations in the S protein are becoming more frequent as the pandemic spreads and that these mutations can have an increased capacity to spread [51,52]. To date, most serum samples from either volunteers in vaccines trials or patients recovering from COVID-19 have shown full or slightly diminished capacity to inactivate some of the more widespread SARS-CoV-2 variants, except for B.1.1.7 (N501Y substitution), 501Y.V2 (N501Y, K417N and E484K substitutions) and 501.V3 (N501Y and E484K substitutions), which have been able to cause a decrease in the neutralization assays using the aforementioned serum samples [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a lot of attention has been focused on RBD mutation E484K, which has emerged in multiple independently SARS-CoV-2 lineages 63, 64 and can alter the antigenicity of the spike protein [65][66][67] . Another naturally occurring RBD mutation, K417N, which has emerged in South Africa and Brazil (B.1.351 lineage and B.1.1.28, respectively) 63, 64,68 , has recently been shown to also alter antigenicity of the spike protein 66,[69][70][71] . Consistently, we found that K417N dramatically decreased the binding of COV107-23 (clonotype 1) and COVD21-C8 (clonotype 2)…”
Section: Discussionmentioning
confidence: 99%